2019
DOI: 10.1038/s41419-019-1355-1
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 1 promotes radioresistance in esophageal squamous cell carcinoma cell lines by modulating autophagy

Abstract: Resistance to radiotherapy results in relapse and treatment failure in locally advanced esophageal squamous cell carcinoma (ESCC). High mobility group box 1 (HMGB1) is reported to be associated with the radioresistance in bladder and breast cancer. However, the role of HMGB1 in the radiotherapy response in ESCC has not been fully elucidated. Here, we investigated the role of HMGB1 to radioresistance in ESCC clinical samples and cell lines. We found that HMGB1 expression was associated with tumor recurrence aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…However, the induction of ICD does not always abrogate tumor growthand may even induce tumor progression in some cancers. [20][21][22] Hence, determining the optimal doses, fractions and schedules of radiotherapy may help counter the negative effects of DAMPs after radiotherapy.…”
Section: Generation Of Immunogenic Cell Death After Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the induction of ICD does not always abrogate tumor growthand may even induce tumor progression in some cancers. [20][21][22] Hence, determining the optimal doses, fractions and schedules of radiotherapy may help counter the negative effects of DAMPs after radiotherapy.…”
Section: Generation Of Immunogenic Cell Death After Radiotherapymentioning
confidence: 99%
“…Immunogenic DAMPs released as a consequence of radiotherapy act as potent inducers to prime innate and adaptive antitumor immune responses. However, the induction of ICD does not always abrogate tumor growth – and may even induce tumor progression in some cancers 20–22 . Hence, determining the optimal doses, fractions and schedules of radiotherapy may help counter the negative effects of DAMPs after radiotherapy.…”
Section: Generation Of Immunogenic Cell Death After Radiotherapymentioning
confidence: 99%
“…Accumulated evidence showed that increased autophagy is an adaptive response that contributes to the acquisition of radiation resistance in cancer 27 . Indeed, we observed IR-resistant cells with high expression of KCNQ1OT1 enhanced autophagy activity compared to their parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, activation of autophagy with the mTORC1 inhibitor rapamcyin augmented cell death in response to combination of nimotuzumab with either cisplatin or paclitaxel. In EAC, treatment with lapatinib, a small molecule inhibitor of EGFR, was associated with induction of autophagy in OE19 cells in vitro, and pharmacological autophagy inhibition potentiated lapatinib-mediated cytotoxicity [73]. Additionally, basal autophagy flux was elevated in Lapatinib-resistant OE19 cells as compared to parental controls, and cell viability was decreased by autophagy inhibition alone or in combination with lapatinib.…”
Section: Roles For Autophagy In Esophageal Cancer Responses To Thementioning
confidence: 99%